Effect Of Rice Planting Practices On Weed Diversity In Seberang Perai And Muda Rice Granaries - Adnan, Aqilah (2014)
The problem of weed infestation in rice fields has been induced by the dramatic change of cultural practices from manual transplanting to direct seeding in rice field of Peninsular Malaysia in the late 1980s. The study on different rice planting practices effect on weed succession in Seberang Perai and Muda rice fields were conducted from September 2011 to January 2013 which involved surveys and experiments in field and glasshouse at MARDI Seberang Perai. Masalah serangan rumpai di sawah padi telah didorong oleh perubahan secara nyata oleh kultura penanaman secara manual kepada kaedah penanaman secara tabur terus di sawah padi Semenanjung Malaysia pada lewat 1980an. Kajian terhadap kesan-kesan perbezaan kaedah penanaman padi ke atas sesaran rumpai di Seberang Perai dan kawasan Muda telah dijalankan sejak September 2011 sehingga Januari 2013.